2012
DOI: 10.25225/fozo.v61.i1.a12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Role of complement regulatory proteins CD46, CD55 and CD59 in reproduction

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 89 publications
1
8
0
1
Order By: Relevance
“…Interestingly, it has been shown that mouse sperm depleted in the CD46 protein [63] have an increased rate of spontaneous acrosome reaction that is initiated in the absence of zona pellucida. This observation correlated with the research done on field mice (genus Apodemus) in which sperm displayed a high rate of spontaneous acrosome reaction due to the absence of the CD46 protein [64][65][66]. The above supports the theory that the CD46 protein participates in acrosome stability, possibly in conjunction with β1 integrins.…”
Section: The Role Of Integrins In Membrane Reorganization and Stabilitysupporting
confidence: 86%
“…Interestingly, it has been shown that mouse sperm depleted in the CD46 protein [63] have an increased rate of spontaneous acrosome reaction that is initiated in the absence of zona pellucida. This observation correlated with the research done on field mice (genus Apodemus) in which sperm displayed a high rate of spontaneous acrosome reaction due to the absence of the CD46 protein [64][65][66]. The above supports the theory that the CD46 protein participates in acrosome stability, possibly in conjunction with β1 integrins.…”
Section: The Role Of Integrins In Membrane Reorganization and Stabilitysupporting
confidence: 86%
“…Interestingly, Tas1r3 expression in testis was~two-fold higher than that in the tongue where this receptor was originally detected. This expression pattern of Tas1r3 resembles the one of Cd46 [27], which was used as a positive control due to its abundant expression in testes and its well described role in fertilization of mammals especially rodents [7,8,28,29]. The result of mRNA gene expression ( Figure 1) suggests that the mTAS1R3 receptor, similar to CD46, is expressed in testes including male germ cells; therefore, it could be predicted to be involved in sperm-related fertilization strategies.…”
Section: The Analysis Of Mrna Expression Of Tas1r3 Gene In Mouse Tissuementioning
confidence: 87%
“…is a crucial step enabling sperm to become fusion competent. During AR, a dramatic reorganization of sperm head membranes occurs including fusion of plasma and outer acrosomal membranes, in order to release the acrosomal content leaving the sperm head surface covered with inner acrosomal membrane (IAM) exposing new proteins [30][31][32][33] . During this event, many of the membrane proteins originally locked in the acrosome relocate to the plasma membrane and different sperm head compartments, mainly to the equatorial segment.…”
mentioning
confidence: 99%